Exporting Roadblocks: Understanding why SMEs in Pakistan are Unable to Compete in Global Markets - BURNEY, SARAH HASAN (2025)
The research examines the export obstacles that small and medium-sized enterprises (SMEs) encounter in Pakistan. While this sector remains essential for economic growth, Pakistani SMEs continue to have a limited presence in international markets. The study investigates external institutional barriers such as ineffective regulations, unstable currency, and inadequate infrastructure in terms of the Resource-Based View (RBV) and Institutional Theory, while analysing their impact on internal issues including export expertise limitations, financial constraints, and outdated technology usage. The introduction of various legislative initiatives has not resolved the ongoing difficulties that prevent Pakistani small and medium-sized businesses from successful global trade participation. The research employs eight semi-structured interviews to develop context-specific knowledge about these challenges through qualitative methodology. The research shows that weak institutional environments directly lead to internal resource deficiencies which prevent export preparation. The research delivers targeted recommendations to help Pakistani SMEs engage internationally, while providing practical insights that benefit both business operations and export-driven policy development.